RANCANG BANGUN APLIKASI WEBSITE MANGROVE PADA KAWASAN PAMURBAYA SURABAYA MENGGUNAKAN METODE SCRUM - Pradhana, Ilham Gilang; Hariadi, Bambang; Eko Wulandari, Sri Hariani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
PAMURBAYA area is expected to be a place or means of learning for the community and also as a mangrove conservation activity so that the community can know the importance of conserving mangrove forests for the city of Surabaya. There are several ways of the process of delivering information about the importance of mangroves for the city which is currently run by the manager of PAMURBAYA wiasata areas such as the existence of information space in the PAMURBAYA area, there is also a learning application "SMART Mangrove" based on Computer aided Instruction (CAI) using Interactive CD. However, from a number of ways the delivery of information is still less effective and efficient because the delivery of information is still not fully accessible to the people of Surabaya. Based on the above problems, a media was made that could provide information to the public in a broad and quickly accessible manner so that the public could know the importance of preserving mangroves. Therefore, an interactive mangrove website was created in the PAMURBAYA area. The results of this application are providing information about the importance of preserving mangroves, loading the types of flora and fauna that exist in the PAMURBAYA Surabaya area, providing information about activities and news in the PAMURBAYA Surabaya area, providing information about the damage that occurred in the PAMURBAYA Surabaya area, the public can also propose activities and references about mangroves as well as providing quizzes that can be played by users of this website.